2018
DOI: 10.1007/s10815-018-1343-x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle mediated embryo-endometrial cross talk during implantation and in pregnancy

Abstract: Extracellular vesicles are lipoproteinaceous membrane-enclosed nanometer-sized structures produced by cells and are thought to mediate cellular communications. Loaded with a specific set of miRNA and protein depending on their tissue of origin, these extracellular vesicles modulate diverse set of biological processes in their target tissues. In recent years, data has gathered on the roles of extracellular vesicles in embryo implantation and pregnancy. Embryo, oviduct, endometrial epithelium and stroma/ decidua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 62 publications
0
100
0
Order By: Relevance
“…Many studies have shown that PA is a specific activator of type I phosphatidylinositol 4-phosphate 5-kinase (PIP5K), which stimulates phosphatidylinositol (4,5) bisphosphate PI(4,5)P 2 production. PA is a positive regulator of PI(4,5)P2, resulting in the accumulation of PA and PI(4,5)P2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that PA is a specific activator of type I phosphatidylinositol 4-phosphate 5-kinase (PIP5K), which stimulates phosphatidylinositol (4,5) bisphosphate PI(4,5)P 2 production. PA is a positive regulator of PI(4,5)P2, resulting in the accumulation of PA and PI(4,5)P2.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), such as microvesicles and exosomes, were found to play key roles in embryo implantation, pregnancy, and parturition in recent studies [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that endometrial epithelial cells treated with the hormones estrogen and progesterone begin to generate EVs. When these vesicles were isolated and then used to treat cultures of trophoblasts, the cell adhesion protein focal adhesion kinase (FAK) became activated and the adhesive capacity of the trophoblasts was increased, suggesting that EVs generated by maternal tissues may play a role during the implantation process …”
Section: Introductionmentioning
confidence: 99%
“…exosomes of uterine luminal fluid (ULF) are capable of mediating embryo-endometrium cross-talk during implantation [8]. Therefore, in order to improve the rate of successful implantation in pigs, it is necessary to investigate the mechanism by which ULF exosomes regulate the cross-talk.…”
mentioning
confidence: 99%